Construction of a simulated dynamic model of data packet routing on a telecommunication network fragment - Turovsky, Oleksandr; Zakharzhevskyi, Andrii; Makarenko, Anatoliy; Dakova, Larysa (Eastern-European Journal of Enterprise Technologies, 2023)
The object of the current research is the process of routing data packets in a telecommunications network. It was established that the state and parameters of data transmission channels and routers could have a negative impact and need to be taken into account in the process of modeling the routing of data packets in telecommunication networks. A model of simulated dynamic modeling of data packet routing in telecommunication networks has been devised and proposed. The suggested model makes it possible to establish quantitative values of the delay time of processing data packets during their routing along a separate segment of the telecommunications network, taking into account the state and parameters of the data transmission channel and routers. It has been established that the achievement of the minimum delay time of data packets during routing is achieved by choosing the path of their transmission under the condition of minimum transmission time by communication lines and the capabilities of routers in terms of their accumulation and service speed. At the same time, the reduction of packet transmission delay time relative to the average for the time network segment can reach from 21 to 38 percent. It is shown that the main factor affecting the value of the delay time is the speed of data processing along the selected path of packet transmission. The number of routing nodes in a separate data transmission path can affect the delay time only if the parameters of the routers are equal compared to others that are included in alternative routes. The model of simulated dynamic modeling of data packet routing reported in this work, unlike the existing ones, takes into account the state and parameters of data transmission channels and routers. It can be used in practical improvement of existing and development of new multi-service telecommunication communication networks